Government Oversight and Economic Impacts: Sustainability in the Vineyard and the Evolution of Wine Regulations, Trade and Production - Anca Alexandra Ducman; Vlad Diaconita; Iuliana Simonca; Anda Belciu; Alexandra Maria Ioana Corbea (Agronomy, 2023)
This study explores the evolution of wine regulations, trade, and production, with a particular focus on the European Union countries and associated countries. The primary objective is to analyze how historical, regulatory, and economic factors have influenced the wine industry from antiquity to modern times. We assess the administrative role of wine in Roman society, its governance in medieval Europe, and the formation of contemporary regulatory frameworks, such as the EU’s Protected Designation of Origin (PDO) system. The study employs a systematic review approach inspired by the PRISMA 2020 statement, incorporating a diverse array of academic journals, historical texts, and statistical data. We use k-means clustering and Principal Component Analysis (PCA) to analyze 2020 production data and value comparisons among European wine varieties. This quantitative analysis reveals patterns in production and trade profiles across European countries, highlighting Romania’s unique position in the non-PDO segment and its strategic balance of wine production and value. The paper also examines the impact of climate change on viticulture and the industry’s response to sustainability challenges. By integrating historical insights with contemporary data, our research provides a comprehensive view of the wine industry’s evolution, emphasizing the interplay of government oversight, market dynamics, and environmental considerations in shaping the European wine landscape.